2011
DOI: 10.1080/00438243.2011.579483
|View full text |Cite
|
Sign up to set email alerts
|

Road my body goes: re-creating ancestors from stone at the greatmoaiquarry of Rano Raraku, Rapa Nui (Easter Island)

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
7
0
2
Order By: Relevance
“…Rano Raraku is a broad volcanic cone rising from an open plain in the south east of Rapa Nui (27°07′S, 109°17′W). It was the main source of the volcanic tuff used for moai (anthropomorphic statues) carving (Richards et al., 2011). Most red-tailed tropicbird nests are associated with moais or rocks (considered to be protected), others are situated on the slopes dominated by the introduced molasses grass (Flores et al., 2017; considered to be exposed).…”
Section: Methodsmentioning
confidence: 99%
“…Rano Raraku is a broad volcanic cone rising from an open plain in the south east of Rapa Nui (27°07′S, 109°17′W). It was the main source of the volcanic tuff used for moai (anthropomorphic statues) carving (Richards et al., 2011). Most red-tailed tropicbird nests are associated with moais or rocks (considered to be protected), others are situated on the slopes dominated by the introduced molasses grass (Flores et al., 2017; considered to be exposed).…”
Section: Methodsmentioning
confidence: 99%
“…While many moai (ca. 400) remain at the statue quarry at Rano Raraku, hundreds of moai , weighing several tons each, were transported along statue roads and erected upon ahu [5355]. In addition, many moai were also adorned with large red-scoria ‘hats’ called pukao [56,57].…”
Section: Background To Rapa Nui and Its Monumentsmentioning
confidence: 99%
“…concluded that the moai quarry shows evidence of multiple independent work areas [e.g., 9,103,104]. Similarly, obsidian was an important raw material available from four source locations on the southwestern part of the island, and obsidian artifacts are abundant in archaeological contexts across the island [105].…”
Section: Plos Onementioning
confidence: 99%